“Aindiados”, indigenous people and politics on the Buenos Aires frontier, 1827-1830 (Quinto Sol, 2013)
This work focuses on the study of a particular type of voluntary insertion of foreigners –the “aindiados”– living among indigenous groups during the 1820s and 1830s, a stage in which the entry and massive settlement of groups from Araucanía took place in the Pampean region. Its extra-regional genesis will be revised and the case of Juan de Dios Montero and his company will be examined in particular.
Keywords: indigenous peoples; aindiados; Buenos Aires frontier; conflicts